Peran Badan Anggaran dan Pengawasan dalam Pembahasan Sistem Perubahan Anggaran - Karolina Mustika Elan Dua; Emilianus Eo Kutu Goo; Nunsio Handrian Meylano (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
This research aims to find out the role of the budget and supervisory body in discussing the budget change system. To identify problems, this research uses qualitative research. Data collection techniques use interviews, observation and document study. It can be concluded that Budget changes are the process of adjusting previously approved budget allocations due to changes in conditions, priority needs, or realization of income and expenditure that is not in accordance with the initial plan. The budget change system refers to the mechanism that regulates how the government or organization implements the plan that regulates how the government or organization implements the agreed budget plan. Agreed budget. This process aims to align the budget with actual conditions, such as changes in economic assumptions, the reality of spending and revenues, or urgent needs.